Significance of N-terminal pro-B-type natriuretic peptide levels in lung cancer - Sinem İnan; Semra Bilaçeroğlu; Burcu Uludağ Artun (Monaldi Archives for Chest Disease)
High blood levels of N-terminal pro-brain natriuretic peptide (NT-proBNP) have been shown in various malignancies. In lung cancer, the importance of NT-proBNP is not clear. In this study, we aimed to investigate the significance of the correlation of NT-proBNP levels in lung cancer with tumor stage, tumor diameter, histopathology, and specific sites of mediastinal metastasis: lymphadenopathy; pericardial, cardiac, major vessel, other mediastinal organ or lymphatic involvement/invasion. A total of 105 lung cancer and 120 control patients (chronic obstructive lung disease, interstitial lung disease, pulmonary thromboembolism, and pneumonia; 30/subgroup) with measured NT-proBNP levels were included retrospectively. Demographics, comorbidities, and echocardiographic findings in all patients, as well as histologic subtype, diameter, stage, and radiologic and/or pathologic mediastinal involvement/invasion of the tumor to the mediastinum in patients with lung cancer, were studied with regards to blood NT-proBNP levels. When lung cancer and control groups were compared globally or as subgroups with comorbidities, NT-proBNP levels did not show meaningful differences. However, NT-proBNP levels were determined to be 249 pg/mL and 88 pg/mL in lung cancer (n=68) and control subgroups (n=58) without comorbidities, respectively (p=0.001). Among lung cancer patients without comorbidities and those with cardiac, pericardial, major vascular, or other mediastinal involvement/invasion (lymphadenopathy, lymphatic, or other organ invasion) (n=27), the NT-proBNP level was 303 pg/mL, whereas it was 166 pg/mL in those without these mediastinal invasions (n=41) (p=0.031). There is a need for much larger, randomized studies to obtain evidence for the potential role of NT-proBNP as a helpful diagnostic biomarker for lung cancer. Clinical suspicion of malignancy may be posed if high NT-proBNP levels cannot be explained by all other risk factors and disorders or diseases. Furthermore, pericardial, cardiac, major vessel, or other mediastinal invasion/involvement should be sought when high NT-proBNP levels are determined in lung cancer patients without any comorbidities or risk factors for high NT-proBNP levels.